RETINAL REATTACHMENT OF SCLERAL BUCKLING WITH OR WITHOUT SUTURES FOR RHEGMATOGENOUS RETINAL DETACHMENT AT CIPTO MANGUNKUSUMO NATIONAL GENERAL HOSPITAL IN INDONESIA - Wirawan Adikusuma; Gitalisa Andayani Adriono; Andi Arus Victor; Ari Djatikusumo; Anggun Rama Yudantha; Mario Marbungaran Hutapea; Sita Paramita Ayuningtyas; Filza Amara Kamila Harlena (Indonesian Vitreoretinal Society, 2026)
Introduction: Rhegmatogenous Retinal Detachment (RRD) is a common, vision-threatening condition traditionally managed by Scleral Buckling (SB), Pars Plana Vitrectomy (PPV), or Pneumatic Retinopexy. SB is effective, however, it carries risks such as strabismus and buckle extrusion, often linked to the use of sutures. This study aimed to determine the outcomes and compare complications of SB with and without sutures for primary RRD cases. Methods: This was a retrospective, analytical cross-sectional study of 65 patients who underwent primary SB (alone or combined with PPV) at Cipto Mangunkusumo National General Hospital (RSCM) from January 2023 to December 2024. Data on demographics, clinical factors, anatomical success (retinal reattachment), functional success (BCVA), and complications were collected and analyzed using descriptive statistics and comparative tests (Chi-square, t-test/Mann-Whitney). Result: During the period, 65 RRD patients underwent the SB procedure. Subjects included 28 cases with sutures and 37 cases without. The mean age was 32.88 years, with a majority of male patients (73.8%) with a mean RRD duration of 17.82 weeks. Preoperative clinical findings showed a high rate of myopia, phakic status, RRD extent in 1 and 4 quadrants, single tear, macula-on, and PVR grade A, with preoperative visual acuity of 1.49 logMAR. The overall anatomical success rate was 76.9%. Statistically, there was no significant difference in retinal reattachment success between SB without sutures (75.7%) and SB with sutures (78.6%) (p=0.784). No demographic or clinical factors was found to significantly predict reattachment success. Postoperative complications included cataract (24.6%) and glaucoma (21.5%). Strabismus (4.61%) was only found in the SB with sutures group. No buckle extrusion occurred in either group. Conclusion: Scleral buckling provides a high enough anatomical success rate for RRD. The SB without sutures technique is equally effective in achieving retinal reattachment and shows a lower incidence of strabismus compared to SB with sutures, making it a viable option for RRD management.